An Updated Review: Androgens and Cognitive Impairment in Older Men - Cai, Zhonglin; Li, Hongjun (Frontiers in Endocrinology, 2020)
Androgens are some of the most important sex hormones in men, and they maintain important physiological activities in the human body. Cognitive impairment is one of the most common manifestations of aging in the elderly population and an important factor affecting the quality of life of elderly individuals. The levels of sex hormones in elderly people decrease with age, and low levels of androgens in older male individuals have been closely linked to the development of cognitive impairment. Basic studies have shown that androgens have neuroprotective effects and that androgen deficiency impairs cognitive function by increasing oxidative stress and decreasing synaptic plasticity, among other effects. Additionally, clinical studies have also shown that androgen deficiency is closely related to cognitive impairment. This article reviews the relationship between low androgen levels and cognitive impairment, their potential mechanisms and the effects of testosterone supplementation in improving cognition.